2020
DOI: 10.21203/rs.3.rs-15885/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miR-128-3p enhances the protective effect of dexmedetomidine on acute lung injury in septic mice by targeted inhibition of MAPK14

Abstract: Background: To investigate the mechanism of miR-128-3p and MAPK14 on the protective effect of dexmedetomidine on acute lung injury in septic mice.Methods: SPF C57BL/6 mice were divided into 8 groups. The pathological changes and wet/dry weight ratio (W/D), PaO2, PaCO2, MDA, SOD and MPO levels in lung tissue and the serum levels of inflammation factors were observed. Dual luciferase reporter assay was used to verify the targeting relationship between miR-128-3p and MAPK14. qPCR and WB were used to detect the ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Ding et al's animal experiments revealed that the expression of MAPK14 in septic mice was significantly higher than that in healthy control mice. Moreover, miR-128-3p can enhance the protective effect of dexmedetomidine on acute lung injury in septic mice by inhibiting the expression of MAPK14 (38). In addition to TLR4 as a marker of early diagnosis of sepsis, Maiti et al found that lumican (an extracellular matrix protein) promoted TLR4 response to bacterial lipopolysaccharides but restricts nucleic acid-specific TLR9 in macrophages and dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ding et al's animal experiments revealed that the expression of MAPK14 in septic mice was significantly higher than that in healthy control mice. Moreover, miR-128-3p can enhance the protective effect of dexmedetomidine on acute lung injury in septic mice by inhibiting the expression of MAPK14 (38). In addition to TLR4 as a marker of early diagnosis of sepsis, Maiti et al found that lumican (an extracellular matrix protein) promoted TLR4 response to bacterial lipopolysaccharides but restricts nucleic acid-specific TLR9 in macrophages and dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al.’s animal experiments revealed that the expression of MAPK14 in septic mice was significantly higher than that in healthy control mice. Moreover, miR-128-3p can enhance the protective effect of dexmedetomidine on acute lung injury in septic mice by inhibiting the expression of MAPK14 ( 38 ). In addition to TLR4 as a marker of early diagnosis of sepsis, Maiti et al.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of PIK3CA and PIK3R1 could exert antiinflammatory effects and treat cough (21). Inhibitors (22). EGFR activators play an essential role in maintaining human bronchial epithelial cell homeostasis (23).…”
Section: Potential Therapeutic Mechanismmentioning
confidence: 99%